Incidence of postoperative urinary retention after pelvic organ prolapse surgery in Cipto Mangunkusumo National General Hospital (Faculty of Medicine Universitas Indonesia, 2014)
Background: After vaginal delivery, every woman has 50% risk for pelvic organ prolapse (POP). The lifetime risk for a woman to undergo surgical treatment for POP was 11%, with the incidence of postoperative urinary retention (POUR) after POP surgery of 2%-43%. The aim of our study is to identify the incidence of POUR after POP surgery in Cipto Mangunkusumo National General Hospital (RSCM) and the risk factors.Methods: Medical records of 124 women undergoing pelvic prolapse surgery between 2010 and 2013 were analyzed. The incidence of POUR and the risk factors were identified by performing univariate and bivariate analysis using chi-Square test and its alternative with using SPSS 20.0. Independent variables include age, body mass index (BMI), parity, degree of prolapse, type of surgery technique, type of anesthesia, type of suture material, amount of intra-operative blood loss, and duration of surgery. POUR defined as urine residual volume more than 100cc.Results: The incidence of urinary retention after pelvic prolapse surgery was 29%. There was no correlation between age, BMI, parity, degree of prolapse, type of surgery technique, anesthesia, suture, intra-operative blood loss, duration of surgery, and the occurrence of urinary retention after pelvic organ prolapse surgery.Conclusion: The incidence of urinary retention after pelvic organ prolapse surgery was 29%. There was no correlation between the risk factors and the occurrence of urinary retention after pelvic organ prolapse surgery.